Female backcountry cordel writers and the organization of a space of speech within the female cordel - Marina Dantas de Figueiredo (Instituto Brasileiro de Estudos e Pesquisas Sociais, 2021)
The right to speak, as the right to express oneself and have its narrative and interpretation of the lived reality considered, have historically been denied or hindered by particular social groups. Backcountry women, over whom categories of oppression intersect, continue to struggle against inheritances of structural gender inequality and of those who place the Brazilian countryside in subordinate structural conditions. Our objective in this study is to propose the idea of ‘spaces of speech’ to analyze the search for the legitimation of forms of knowledge production, within the scope of the daily practices of confrontation of female backcountry writers of cordel literature, in the form of collective or individualized subjective expressions, in the context of cordel literature. We conducted a qualitative research, based on documentary analysis, and non-participant observation, to understand how the literary practice of backcountry woman is a speech space. In a contribution to the theory of place of speech, we conclude that the organization of cordel literature as a ‘speech space’ goes through (1) female appropriation of cordel as a means of claim, which assumes the role of written representation of the speech of backcountry women; (2) search for recognition of female backcountry writers, individually, in the cordel literary scene; and (3) relationship with political activism around women’s issues and feminist vocabulary.